Pengaruh Proporsi Komisaris Independen, Jumlah Direktur, Jumlah Komite Audit, Kepemilikan Saham Institusional, Kepemilikan Saham Manajemen Dan Ukuran Perusahaan Terhadap Kinerja Keuangan Perusahaan - Herman Ruslim; Ieneke Santoso (Jurnal Ekonomi, 2018)
This study aims to test the impact of the independent commissioners, board of directors, audit committee, ownership of institutional and management shares and size of the firm on the firm performance of the firms listed at Indonesian Stock Exchange Index LQ45 for two consecutive years of the period  February 2014 to January 2016.  This study uses the sampling data of 31 firms.  The sampling is based on the method of purposive sampling.  The process of analyzing data is carried out with analysis partially first and then analysis simultaneous. The statistic method used is SPPS ( Statistical Product and Service Solution) to obtain descriptive statistics, correlation of variables and analysis of variance. The result of the partial analysis shows that there are two variables has a significant influence on the firm performance which is a portion of independent commissioner and ownership of institutional shares.  Whereas, the result of the simultaneous analysis has shown a significant impact.